A study of the short-term responses of fynbos to fire in the Kogelberg State Forest, South Africa - Durand, Barend Jacobus (Department of Biological Sciences, 2024)
The physical environment of a fynbos community was measured from before the experiments began and the work is continuing. Prior to burning 0, 25 ha-, and s I ightl y smaller plots..,were I aid out in an approximately 20 year old proteoid-ericoid-restioid community. The community 1s physiognomy and structure were described with methods that are compatible with the vegetation. Al I vegetation and environmental parameters that were measured confirm the classification of the fynbos that it is an evergreen broad to narrow leaved sclerophyl lous shrub land with rest ioid, ericoid and proteoid elements (Taylor, 1978). Experimental burns in al I the seasons, except winter, indicated that the timing of burning for catchment management is very important. Summer and spring burns, in that sequence, have the least short-term effect on fynbos species composition and the rate of vegetative recovery. Autumn fires suppress both the recovery of the vegetation and species survival. The phenology of species in the fynbos is changed for at least one season after a fire. Geophytes are stimulated to flower in abundance after a summer burn but much less so by a spring burn. The spring burn prevented at least one geophyte species from flowering the fol lowing spring which is the flowering time for the species. Records for the autumn burn are from too short a time after a burn for conclusions, but the regrowth of Rest io egregius was slower than for any of the other treatments. Flowering maturity is concomitantly retarded. Fi re intensities varied between the seasons, but the greatest factor determining intensity was rather the amount of fuel available per unit area than the season of the burn. composition also determines the heat value of the fuel.